Novel applications of organic fluorophores: White light emission, chemosensor and ambient microdroplet synthesis / Norfatirah Muhamad Sarih - Norfatirah , Muhamad Sarih (2021)
This thesis has focused on the applications of organic fluorophore for producing white light emission, developing a fluorescence-based sensor of Fe3+ and a new method for the accelerated synthesis of dansyl aniline (DA). The first work in this research relates to a novel means to generate white light emission (WLE) by mixing three fluorescent organic compounds; furocoumarin (FC), DA, and 7-hydroxycoumarin-3-carboxylic acid (CC). This novel mixture is immobilised in silica aerogel and applied as a coating to a UV LED to demonstrate its applicability as a low-cost, organic coating for WLE via simultaneous emission. Kept in an ethanol solution while immobilised in silica aerogel, the mixture exhibits a Commission Internationale d’Eclairage (CIE) chromaticity index of (0.27,0.33). It was observed that a broadband and simultaneous emission involving CC, FC and DA played a vital role in obtaining a CIE index close to that of pure white light. The next application uses coumarin derivatives to develop a novel chemosensor for the sensitive and selective detection of Fe3+. Furocoumarin (furo[3,2-c]coumarin) derivatives have been synthesised from a single step, high yielding (82-92%) chemistry involving a 4- hydroxycoumarin [4+1] cycloaddition reaction. They were characterised by FTIR, 1HNMR, and, for the first time, a comprehensive UV-Vis and fluorescence spectroscopy study was carried out to determine if such compounds can serve as useful sensors. Based on the fluorescence data, the most promising furocoumarin derivative (2- (cyclohexylamino)-3-phenyl-4H-furo[3,2-c]chromen-4-one, FH), exhibits strong fluorescence (Фf = 0.48) with long fluorescence lifetime (5.6 ns) and large Stokes’ shift, suggesting FH could be used as a novel fluorescent chemosensor. FH exhibits a highly selective, sensitive, and instant turn-off fluorescence response to Fe3+ over other metal ions which is attributed to a charge transfer mechanism. Selectivity is demonstrated against 13 other competing metal ions (Na+, K+, Mg2+, Ca2+, Mn2+, Fe2+, Al3+, Ni2+, Cu2+,Zn2+, Co2+, Pb2+ and Ru3+) and aqueous compatibility is demonstrated in a 10% MeOHH2O solution. This novel sensor has a limit of detection of 1.93 μM, below that of the US environmental protection agency guidelines (5.37 μM), with a linear dynamic range of~28 (~2−30 μM) and an R2 value of 0.9975. As an exemplar application, the potential of this sensor was demonstrated for the rapid measurement of Fe3+ in mineral and tap water samples, establishing the real-world application of FH as a “turn off” fluorescence sensor. Lastly, the research is expended to discover the nucleophilic substitution reactions of dansyl aniline by reactive paper spray ionisation-mass spectrometry (PSI-MS). PSI-MS is an emerging tool for ambient reaction monitoring via micro droplet reaction acceleration. PSI was used to accelerate and monitor the time course of the reaction of dansyl chloride with aniline, in acetonitrile, to produce dansyl aniline. Three distinct PSI arrangements were explored in this study to represent three types of sample loading and interactions, the conventional single tip as well as two novel setups, dual tip, and a coaxial setup. The effect on product yield was investigated using these different types of paper tips for a range of geometric considerations, including distance of microdroplet travel. It was observed that product yield is increased at a given distance and decreases thereafter for all PSI configurations. Amongst the variety of sample loading methods, the novel dual tip arrangement showed increased product yield which also exhibited the largest microdroplet density. In general, the reaction monitoring by PSI-MS with a dual tip configuration shows much promise and was further utilised for the successful synthesis of a silyl-alkylated dansyl aniline compound demonstrating a rapid and simple optimisation procedure based on ratio concentration adjustments.